Clinical Applications of Doppler Ultrasound in Obstetrics - Rowshan Jawad Azeez (Journal of Global Pharma Technology, 2016)
Ultrasound images of flow, whether color flow or spectral Doppler, are essentially obtained from measurements of movement. In ultrasound scanners, a series of pulses is transmitted to detect movement of blood. Echoes from stationary tissue are the same from pulse to pulse. Echoes from moving scatters exhibit slight differences in the time for the signal to be returned to the receiver. These differences can be measured as a direct time difference or, more usually, in terms of a phase shift from which the ‘Doppler frequency’ is obtained. They are then processed to produce either a color flow display or a Doppler sonogram.